Physiological Study of Udaan Vayu w.s.r Speech - Saini, Mukesh; Sharma, Rajesh Kumar; Sharma, Dinesh Chandra (International Research Journal of Ayurveda & Yoga, 2021)
The purpose of Ayurveda science is to maintain the health of the healthy and cure disease of diseased. In Ayurveda a person is said to be healthy when Dosha, Agni (digestive fire), Dhatu(tissues), all the physiological process are in homeostatic state and soul, sense organ and mind are in a state of total wellbeing. [4] Vata dosha acts as yantratantradhara which means in its normal state it maintains the function of organs and organ systems. [2] Among five Vata Dosha, Udana Vayu is located in urah (thorax region), and travel across Nasa (nasal passage), Nabhi (umbilicus), and gala (throat region). The term Udana itself signifies upward movement of Doshas. Udanavata is considered as Pavanottama. [4] It is responsible for the production of speech, effort, energy and maintenance of strength required for the purpose. It also helps in remembrance of vocabulary required to make the speech meaningful. All the functions of udana vayu can be compared with physiological functions of anatomical structure of contemporary modern medical science. Basically Broca’s area, Wernicke’s area, thymus gland, serotonin like happy hormone, motor area of cerebral cortex and other structures might be compared with the functions of udana vayu. [10]